2009
DOI: 10.1007/s11852-009-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Forest structure of arid zone mangroves in relation to their physical and chemical environment in the western Gulf of Kachchh, Gujarat, Northwest coast of India

Abstract: To understand natural and anthropic control of mangrove vegetation in the Gulf of Kachchh, a study was undertaken of its vegetation structure. Over 2 years (1999)(2000) at three sites, mangrove vegetation was studied, including tree density, tree height, tree girth at breast height (GBH), canopy index, regeneration class and recruitment class, together with physico-chemical characteristics of water and sediment and the textural aspects of sediments. Reflecting the hot, arid hinterland of Gujarat, ambient tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…), 2·9–25·6 g kg −1 in India (Saravanakumar et al . ) and 82·0–185·6 g kg −1 in Brazil mangrove soils (Prada‐Gamero et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), 2·9–25·6 g kg −1 in India (Saravanakumar et al . ) and 82·0–185·6 g kg −1 in Brazil mangrove soils (Prada‐Gamero et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the organic matter content of these ecosystems varies widely with location, but generally is medium to high. Organic carbon contents of 23Á8-102Á8 g kg À1 were reported in China (Zhang et al 2009), 2Á9-25Á6 g kg À1 in India (Saravanakumar et al 2009) and 82Á0-185Á6 g kg À1 in Brazil mangrove soils (Prada-Gamero et al 2004). Variations from 2Á0 to 13Á6 g kg À1 in restinga (Oliveira et al 2010) and 30Á3 g kg À1 in the Atlantic Forest soils (Valpassos et al 2007), both from Brazil, have been found.…”
Section: Micro-organism Populationsmentioning
confidence: 96%
“…Thus, a large portion of inflow seawater sinks and becomes subsurface outflow, and only a small portion of Red Sea water could reach Site 8. The restricted circulation contributed to low D.O at S8 due to low solubility in warmer water and stagnant water body (Saravanakumar et al, 2008), and predominance of clay and silt in texture (Table 1).…”
Section: Restricted Circulation To the Southern End Of The Lagoonmentioning
confidence: 99%
“…Mangrove forests are distributed mainly in subtropical and tropical regions and are rarely found in arid regions, where they have to endure more extreme conditions due to the hot and dry climate. Since salinity is correlated positively with temperature and negatively with the amount of precipitation (Saravanakumar et al, 2009), soil salinity is likely to be higher in arid regions (Naidoo et al, 2011). In addition, mangrove forests in arid regions show a lack of nutrients because of the low input of decomposable organic matter and low precipitation (Alongi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%